Current Aspects of Legal Regulation for Monitoring Electronic Communications and Removal of Information from Electronic Communication Networks in Ukraine - V. M. Lazebnyi (Bulletin of Kharkiv National University of Internal Affairs)
The article is focused on studying current aspects of normative and legal regulation for monitoring electronic communications in foreign countries and in Ukraine; on the features of conducting search and investigative actions on the removal of information from electronic communication networks.